Assessment of an application on a detoxification process of groundnut press cake for aflatoxins by ammoniation. (21st December 2021) - ,; Schrenk, Dieter; Bignami, Margherita; Bodin, Laurent; Chipman, James Kevin; del Mazo, Jesus; Grasl‐Kraupp, Bettina; Hoogenboom, Laurentius (Ron); Leblanc, Jean‐Charles; Nebbia, Carlo Stefano; Nielsen, Elsa; Ntzani, Evangelia; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Contaminants in the Food Chain (CONTAM) provided a scientific opinion on an application for a detoxification process of groundnut press cake for aflatoxins by ammoniation. Specifically, it is required that the feed decontamination process is compliant with the acceptability criteria specified in the Commission Regulation (EU) 2015/786 of 19 May 2015. The CONTAM Panel assessed the data provided by the feed business operator with respect to the efficacy of the process to remove the contaminant from groundnut press cake batches and on information demonstrating that the process does not adversely affect the characteristics and the nature of the product. Although according to the literature the process may be able to reduce aflatoxin levels below the legal limits,  the Panel concluded that the proposed decontamination process, on the basis of the experimental data submitted by the feed business operator, cannot be confirmed for compliance with the acceptability criteria provided for in Commission Regulation (EU) 2015/786 of 19 May 2015. The Panel recommended sufficient sample testing before and after the process, under the selected conditions, to ensure that the process is reproducible and reliable and to demonstrate that the detoxification is not reversible. In addition, genotoxicity testing of extracts of the treated feedingstuff and of the identified degradation products would be necessary. Finally, information on the transfer rate of AFB1 to AFM1 excretion in milk for animals fed the ammoniated product, in comparison to the starting material and on the ammoniation process changes of the nutritional values of the feed material should be provided.